BIODELIGNIFIKASI KULIT BUAH KAPUK (CEIBA PENTANDRA (L.) GAERTN) MENGGUNAKAN TRAMETES VERSICOLOR - Mi’rajunnisa Mi’rajunnisa; Yulianita Pratiwi Indah Lestari (Jurnal Inovasi Penelitian, 2022)
This study aims to obtain alpha-celulose from kapok pericarpium using biodelignification of Trametes versicolor. Alpha cellulose was obtained by combination delignification. The biodelignification using Trametes versicolor at 30˚C and 40˚C. To obtained the optimum result, the next procedure was chemical delignification using the Kraft process using 10% NaOH followed by the addition of HNO3 and bleaching using sodium hypochlorite. The purity of the kapok pericarpium alpha-cellulose obtained was determined by dissolving alpha-cellulose kapok rind with 17.5% NaOH, 8.3% NaOH, and 10% acetic acid. Biodelignification carried out at a temperature of 40˚C produced 14.88% α-cellulose, Qualitative analysis using ZnCl2 was showed positive alpha-cellulose from the blue-violet reaction, while the FTIR spectrogram showed that the resulting alpha-cellulose did not contain lignin.